Networks and the organisation of knowledge intensive sectors - Salavisa, I.; Salavisa, I.; Sousa, C.; Fontes, M. (DRUID Society Summer Conference 2011 on Innovation, Strategy, and Structure Organisations, Institutions, Systems and Regions, 2011)
This paper addresses the role of networks in the organisation of two different knowledge intensive sectors - biotechnology and software. Its main aim is to identify and explain the differences in the architecture of the networks, formal and informal, mobilised to access resources and competences by young entrepreneurial firms in those two sectors in Portugal. Then it discusses the diversity of the actual network topologies in the light of their contribution to the organisation of those sectors, taking into account their specific environment. For this purpose, it applies a methodology that permits to assemble a vast array of data capturing the nature and contents of the range of relationships through which key innovation resources flow into the firms. The results show that, when a detailed analysis is carried out, significant inter-sectoral differences emerge, both in the network diagrams and in the measures of composition and structure. We argue that those different topologies make sense regarding the empirical literature and shed light on the specific organisation of the sectors, with their strengths, weaknesses and policy-driven influences.